Thermogravimetric analysis and the optimisation of bio-oil yield from fixed-bed pyrolysis of rice husk using response surface methodology (RSM) - Khairuddin, Md Isa; Suhardy, Daud; Nasrul, Hamidin; Khudzir, Ismail; Saiful Azhar, Saad; Farizul Hafiz, Kasim (Elsevier B.V., 2011)
Link to publisher’s homepage at http://www.elsevier.com/